Impact of Race on Admission, Clinical Outcomes, and Disposition in Cholangiocarcinoma: Insights from the National Inpatient Database - Tijin A. Mathew; Teresa M. Varghese; Nithya Krishnakumaran; George M. Varghese; Khwaja S. Haq; Akshita Khosla; Rojymon Jacob; Gina Vaccaro (Diseases, 2025)
Background: Cholangiocarcinoma, malignancies arising from the intrahepatic and extrahepatic bile ducts, has increased in incidence in the United States over the past few decades. The reported incidence of cholangiocarcinomas is high, particularly in specific racial groups such as Asian and Pacific Islander patients. Race also significantly impacts disparities in healthcare utilization and clinical outcomes. Our study focused on the impact of race on admission, clinical outcomes, and disposition of cholangiocarcinoma. Methods: We performed a retrospective analysis of cholangiocarcinoma-related hospital admissions, using the National Inpatient Sample for the year 2022. Patients were stratified according to race into the following groups: White, African American, Hispanic, Asian or Pacific Islander, Native American, and Other. The data analysis was performed using STATA/BE version 18.5. Univariable and multivariable logistic regression models were applied to evaluate the relationship between race and clinical and healthcare utilization outcomes. Results: In 2022, 7479 hospitalizations were recorded for cholangiocarcinoma in the United States. Among these, 65.99% were White, 13.27% Hispanic, and 10.13% African American. There was a statistically significant difference in gender distribution across racial groups (p < 0.001), with males comprising the majority in all groups. Males outnumbered females in all racial groups except among the Hispanic group. Significant racial disparities in mortality were observed, with White patients showing a mortality rate of 6.69%, compared to higher rates among African American (9.76%), Native American (8.51%), and Asian or Pacific Islander (8.09%) patients, while Hispanic (5.04%) and Other (5.88%) groups had lower rates (p < 0.001). Conclusions: The study underscores the racial disparities among cholangiocarcinoma hospitalizations, with African American, Native American, and Asian patients facing disproportionately higher mortality and poorer in-hospital outcomes compared to White patients. This analysis highlights the healthcare strategies and policy reforms to promote equitable treatment by mitigating these disparities and to improve cholangiocarcinoma outcomes.